2022
DOI: 10.3390/ijerph19052678
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness—Not Physical Activity Levels—Influence Quality of Life in Anorexia Nervosa

Abstract: Background: Incorporating physical activity (PA) has been a challenge for health care professionals working with anorexia nervosa (AN) patients. This has contributed to partial physical fitness (PFit) recovery that persists after weight restoration. Objective: This cross-sectional study aimed to examine the relationships between PA, sedentary behaviors, PFit, and quality of life (QoL) in a group of adolescents after hospitalization. Methods: QoL, PA, and sedentary behaviors were measured using the Health-Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Indeed, it has been observed that various behaviours of an emotional nature arose during lockdown, which could be associated with the high number of injuries observed [ 4 ]. The relationship between exercise and mental health is complex; exercise has been shown to be effective in improving mental health both in the general population and in those with physical or mental illness [ 31 , 32 , 33 ]. Therefore, exercise could have been implemented in our population with the aim of improving participants’ mental well-being and it, combined with higher levels of cortisol, could explain the results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been observed that various behaviours of an emotional nature arose during lockdown, which could be associated with the high number of injuries observed [ 4 ]. The relationship between exercise and mental health is complex; exercise has been shown to be effective in improving mental health both in the general population and in those with physical or mental illness [ 31 , 32 , 33 ]. Therefore, exercise could have been implemented in our population with the aim of improving participants’ mental well-being and it, combined with higher levels of cortisol, could explain the results.…”
Section: Discussionmentioning
confidence: 99%